The Impact of Sovereign Credit Rating Changes on Emerging Stock Markets - YIN, WEIGUO (2008)
This study investigate the impact of sovereign rating change in emerging markets by using 42 sample counties over the period Jan. 1999 to Aug. 2008. The concurrent relationship between sovereign rating changes and the associated stock market spread can be established: the spreads tend to rise (fall) when upgrades (downgrades) occur. Surprisingly, according to Fitch report regarding the emerging market liquidity, we divide the whole time line into two sub-periods. It is found that rating changes in tranquil period (i.e. a stable external financing flow to emerging markets) has no impact on the stock markets returns. However, during the growth period, when arising of the global financing flows to emerging markets, rating downgrades provide strong evidence. For the lead-lag relationship, there is no strong evidence to support the arguments of pro-market-performance conducted by credit rating agencies. An unreasonable finding from our result is rating downing lead the stock markets by up to four months. There is a puzzle in this analysis which could be the future research. We also find market reaction does not depend on the category of rating downgrades, only treat them as negative news. Although there are some evidence found that positive rating changes also have significant impact on the market, the term of rating downgrades is more meaningful than rating upgrades. In the case of downgrades, the market reaction is stronger if a rating downgrade is related to speculative-grade sovereigns rather than investment-grade sovereigns. And the market reaction seems no difference to multiple notch changes and single notch change.